Handbook for Ethiopian public administration program accreditation (LEUVEN UNIVERSITY PRESS, 2022)
Follow-up to the handbook Public Administration in Ethiopia Improving, assuring, and maintaining the quality and relevance of education and training in Public Administration has attracted increasing attention among PA scholars and practitioners worldwide. The Handbook for Ethiopian Public Administration Program Accreditation is a follow-up to the first handbook on Ethiopian Public Administration. The new handbook zooms in on how to improve, assure, and accredit PA education and training programs in Ethiopia. It is consistent with the Pan-Africanism and African Union's Agenda 2063 and contributes to the United Nations Sustainable Development Goals (SDGs), particularly SDGs 4 and 16. Together with the handbook Public Administration in Ethiopia (2020), the current follow-up volume is a valuable stepping stone for PA teaching and PA research in Ethiopia and therefore essential reading for students, practitioners, and theorists interested in public administration, public policy, and sustainable development. Ebook available in Open Access.